Triplax sulphuricollis Reitter, 1887 from the Hyrcanian forests of Iran recognized as a valid species by morphology and barcoding (Coleoptera: Erotylidae) - Thorn, Simon; Kazerani, Farzaneh; Farashiani, Mohammad Ebrahim; Morinière, Jérôme (Zootaxa, 2022)
The status of Triplax collaris sulphuricollis Reitter, 1887 is reevaluated based on recent records from the Hyrcanian forests in northern Iran. Morphological features and barcoding support separate species status as Triplax sulphuricollis Reitter, 1887, new status. Morphological characteristics include an orange-yellow antennal club and elytral punctation arranged in striae. Triplax sulphuricollis is associated with oyster fungi of the genus Pleurotus growing on dead wood of deciduous trees.